Evaluating the Potential for Resistance Development to Antimicrobial Blue Light (at 405 nm) in Gram-Negative Bacteria: In vitro and in vivo Studies - Leanse, Leon G.; Harrington, Olivia D.; Fang, Yanyan; Ahmed, Imran; Goh, Xueping Sharon; Dai, Tianhong (Frontiers in Microbiology, 2018)
Antimicrobial resistance is a threat to public health that requires our immediate attention. With increasing numbers of microbes that are becoming resistant to routinely used antimicrobials, it is vital that we look to other, non-traditional therapies. Antimicrobial blue light (aBL) is an innovative approach that has demonstrated efficacy for the treatment of infections. In the present study, we investigated the potential for resistance development to aBL in Gram-negative pathogenic bacteria by carrying out serial aBL exposures on bacteria. In the first aBL exposure, clinical isolates of Pseudomonas aeruginosa, Acinetobacter baumannii and uropathogenic Escherichia coli (107 colony forming units/mL [CFU/mL]) were irradiated in phosphate-buffered saline with aBL at 405 nm until a >99.99% reduction in bacterial viability was achieved. Irradiation was then repeated for each bacterial species over 20 cycles of aBL exposure. The potential for resistance development to aBL was also investigated in vivo in superficial mouse wounds infected with a bioluminescent strain of P. aeruginosa (PAO1; 108 CFU) and irradiated with a sub-curative radiant exposure of 108 or 216 J/cm2 aBL over 5 cycles of treatment (over 5 days) prior to bacterial isolation from the animal tissue. PAO1 isolated from infected tissue were treated with aBL at 216 J/cm2, in vitro, in parallel with unexposed PAO1 or PAO1 isolates from mouse wound infections not treated with aBL. No statistically significant correlation was found between the aBL-susceptibility of bacteria in vitro and the number of aBL exposures in any bacterial species (P ≥0.26). In addition, serial exposure of infected mouse wounds to aBL did not result in any change in the susceptibility to aBL of PAO1 (P = 0.97). In conclusion, it is unlikely that sequential exposure to aBL will result in aBL-resistance in Gram-negative bacteria. Also, multiple aBL treatments may potentially be administered to an infected wound without resistance development becoming a concern.